2016
DOI: 10.1262/jrd.2015-124
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural comparison of porcine putative embryonic stem cells derived by <i>in vitro</i> fertilization and somatic cell nuclear transfer

Abstract: The ultrastructure of porcine putative embryonic stem cells and porcine fetal fibroblasts (PFFs) was analyzed by transmission electron microscopy. The aim of this study was to compare the features of organelles in in vitro fertilization (IVF) derived porcine embryonic stem cells (IVF-pESCs) and somatic cell nuclear transfer (SCNT) derived pESCs (SCNT-pESCs). Also, the features of organelles in high-passage IVF-pESCs were compared with those in low-passage cells. The ultrastructure of PFFs showed rare microvill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
2
2
0
Order By: Relevance
“…This conversion of energy metabolism was also known to occur during osteogenic differentiation from human mesenchymal stem cells [ 32 ]. Our previous report confirmed that the porcine ESCs in a higher passage have much more initial signs of apoptosis than those in lower passages through TEM analysis [ 33 ]. As porcine ESCs are passaged under stress, some of them exhibit pyknosis, wrinkly nuclear envelopes, and numerous lysosomes associated with autophagic vacuoles.…”
Section: Embryonic Stem Cells and Apoptosissupporting
confidence: 74%
“…This conversion of energy metabolism was also known to occur during osteogenic differentiation from human mesenchymal stem cells [ 32 ]. Our previous report confirmed that the porcine ESCs in a higher passage have much more initial signs of apoptosis than those in lower passages through TEM analysis [ 33 ]. As porcine ESCs are passaged under stress, some of them exhibit pyknosis, wrinkly nuclear envelopes, and numerous lysosomes associated with autophagic vacuoles.…”
Section: Embryonic Stem Cells and Apoptosissupporting
confidence: 74%
“…In the present study, LFCs and LPCs bore abundant microvilli at the apical membranes, which are characteristic features of embryonic stem cells (Baharvand & Matthaei, 2003; Sathananthan et al, 2002; Yoo et al, 2016), epithelial cells of embryoid bodies (Alharbi et al, 2014), and neuroepithelial cells and NPCs during neurogenesis (Marzesco et al, 2005). However, it has rarely been reported in NS (Gil‐Perotín et al, 2013).…”
Section: Discussionsupporting
confidence: 50%
“…The inner cells of the small cysts in the peripheral retina exhibited the following morphological and histochemical features that are similar to pluripotent stem cells such as ES cells and induced pluripotent stem (iPS) cells: (1) a small round shape, (2) a high nuclear/cytoplasmic (N/C) ratio, and (3) a euchromatin-rich nucleus [34][35][36]. Furthermore, the small cysts formed structures closely resembling the preimplantation blastocyst [13], i.e., both the small cyst and the blastocyst were composed of three components: an inner cell mass comprised of extremely small cells, an outer wall consisting of a single layer of It has been reported that vWF is expressed in the trophoblasts derived from the trophectoderm [26][27][28].…”
Section: Discussionmentioning
confidence: 99%